Combat leader's field guide - Kirkham, Jeff (Stackpole Books, 2015)
A guide to the basic skills all soldiers, sailors, and Marines must know to prevail in small-unit dismounted combat operations, including planning, battle drills for offense and defense operations, patrols, construction and emplacement of fighting positions, use of weapons and call for fire, land navigation and map reading, communications, close quarter battle, and tactical combat casualty care.